Ectodermal dysplasia - Maxillary and mandibular alveolar reconstruction with dental rehabilitation: A case report and review of the literature - Sanjeev N. Deshpande; Vikas Kumar (Indian Journal of Plastic Surgery)
Ectodermal dysplasia is a rare group of inherited disorders characterized by aplasia or dysplasia of tissues of ectodermal origin, such as hair, nails, teeth and skin. Dental manifestations include hypodontia, complete anodontia or malformed teeth. Oral rehabilitation is the major surgical challenge in such patients. It frequently requires alveolar reconstruction followed by dental implants. We report a case of hypohidrotic ectodermal dysplasia, which was managed with reconstruction of both the upper and the lower alveolus using free fibula flaps with dental rehabilitation using osseointegrated implants.